2019
DOI: 10.1152/ajpheart.00503.2017
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive aortic remodeling in hypertension associates with dysfunctional smooth muscle contractility

Abstract: Intramural cells are responsible for establishing, maintaining, and restoring the functional capability and structural integrity of the aortic wall. In response to hypertensive loading, these cells tend to increase wall content via extracellular matrix turnover in an attempt to return wall stress and/or material stiffness toward homeostatic values despite the elevated pressure. Using a common rodent model of induced hypertension, we found marked mouse-to-mouse differences in thoracic aortic remodeling over 2–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…= ( , )/ℎ( , )). The role of smooth muscle contraction is consistent with a recent finding in a larger cohort of C57BL/6 mice wherein a small sub-set of DTAs having modest AngII-induced hypertensive remodeling had a well preserved vasoactive capability, at least to KCl (Korneva and Humphrey, 2019). This observation is also consistent with our prior report of regional differences in AngII-induced hypertensive aortic remodeling in Apoe -/mice wherein maladaptive fibrotic remodeling manifested in regions having a lower intrinsic vasoresponsiveness to AngII (Bersi et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…= ( , )/ℎ( , )). The role of smooth muscle contraction is consistent with a recent finding in a larger cohort of C57BL/6 mice wherein a small sub-set of DTAs having modest AngII-induced hypertensive remodeling had a well preserved vasoactive capability, at least to KCl (Korneva and Humphrey, 2019). This observation is also consistent with our prior report of regional differences in AngII-induced hypertensive aortic remodeling in Apoe -/mice wherein maladaptive fibrotic remodeling manifested in regions having a lower intrinsic vasoresponsiveness to AngII (Bersi et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…AngII-induced hypertensive remodeling in C57BL/6 DTAs tends not to differ over two-to-four weeks of infusion (Bersi et al, 2016;Korneva and Humphrey, 2019) and that hypertension induced in C57BL/6;129SvEv mice over longer periods (13 to 18 weeks) using a high salt diet and L-NAME did not cause adverse fibrotic remodeling in the DTAs (Bellini et al, 2015;Spronck et al, 2019). Hence, again, genetic modifiers intrinsic to the 129SvEv strain appear to have a dominant role in attenuating aortic remodeling in multiple models of induced hypertension in…”
Section: Discussionmentioning
confidence: 99%
“…S1, E-H). Since we do not expect inhalation of cigarette smoke to influence axial tethering (27,57), collagen deposition (Fig. 4, E and F) presumably hindered the elastic fiber recoil, reducing the in vivo axial stretch (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In literature, it has been shown that long-term infusion of AngII impairs the voltage-dependent contractions of the thoracic aorta [23]. Dysfunctional smooth muscle cell (SMC) contractility strongly correlates with maladaptive aortic remodeling and fibrosis [24]. Moreover, restoring smooth muscle contractility protects thoracic AD [25], suggesting that preserving contractile capacity may reduce mechanical stress-induced pathological events leading to AA and AD.…”
Section: Introductionmentioning
confidence: 99%